2018
DOI: 10.1007/s41999-017-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of older inpatients in medical student education

Abstract: ObjectivesTo examine older inpatients’ experiences with medical student education, their views on future interactions, and to seek their opinion on the most important curricular topics related to geriatric medicine.MethodsThe study involved 112 non-confused inpatients older than 65 years of age, who completed a uniformed questionnaire on the day of their discharge from a teaching hospital.ResultsThe mean age was 81 years, with equal number of male and female participants. 57% interacted with the students durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…More research is needed to delineate this balance. Only one of 110 patients said the worst part of the teaching was that it was too long, while Aquilina et al found that 23% of patients said their experience was time consuming [19].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More research is needed to delineate this balance. Only one of 110 patients said the worst part of the teaching was that it was too long, while Aquilina et al found that 23% of patients said their experience was time consuming [19].…”
Section: Discussionmentioning
confidence: 99%
“…and N.R. after reviewing the questions asked of patients in previous studies that assessed their experiences [8,10,13,[18][19][20]22] and creating questions that answered specific components of our hypothesis: factors that may affect motivation for participation (adequacy of informed consent, desire to teach students, sense of obligation, boredom), and examination of the quality of the experience (effect on happiness, pain, perception of hospital stay). The survey included 19 statements that were rated by patients on a Likert scale from 1 to 5, and three short answer questions which allowed for free-text answers and comments.…”
Section: Surveymentioning
confidence: 99%
See 3 more Smart Citations